2011
DOI: 10.1016/j.tra.2009.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Road transport and climate change: Stepping off the greenhouse gas

Abstract: Transport is Australia's third largest and second fastest growing source of greenhouse gas (GHG) emissions. The road transport sector makes up 88 percent of total transport emissions and the projected emissions increase from 1990 to 2020 is 64 percent. Achieving prospective emission reduction targets will pose major challenges for the road transport sector. This paper investigates two targets for reducing Australian road transport greenhouse gas emissions, and what they might mean for the sector: emissions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(42 citation statements)
references
References 5 publications
0
40
0
2
Order By: Relevance
“…Achieving reductions in road transport GHG emissions requires a much broader policy response [26]. Although certain policies can respond quickly to the pressure, in reality it is a slow process and there is a growing expectation on how new technologies can deliver the solution [3].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Achieving reductions in road transport GHG emissions requires a much broader policy response [26]. Although certain policies can respond quickly to the pressure, in reality it is a slow process and there is a growing expectation on how new technologies can deliver the solution [3].…”
Section: Resultsmentioning
confidence: 99%
“…For the rest of the year, it is almost hostile to use this option. A target of one quarter of all trips in the major cities in Australia to be undertaken by walking and cycling, compared to the current average share of around 16%, would contribute about 4.4 Mt of the targeted 36 Mt emissions reduction at 2020 [26].…”
Section: Short-term Mitigation Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…In any case, the assessment of the burden exerted by roads on the natural environment needs more comprehensive perspectives that range from climate change analyses [6] to ecosystem preservation [7], with a new attention to the sustainability footprint impacts [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the U.S., it is estimated that achieving GHG emission reductions of 30% below 1990 levels in the year 2050 will end oil imports [10]. An analysis of the Australian road transport GHG emissions [11] has shown that very substantial reductions in fuel carbon intensity are vital to achieve emissions in 2020 being 20% below 2000 levels and emissions in 2050 being 80% below 2000 levels. Although the full replacement of fossil fuels by biofuels is not deemed to be achievable, modern biofuels have a crucial role to fulfil in helping the long-term limit to growth of GHG emissions and to lead the transition of the current petroleum-based society towards a more sustainable one [12].…”
Section: Introductionmentioning
confidence: 99%